NEEDS ANALYSIS OF VOCATIONAL HIGH SCHOOL TEXTBOOK TO LOCAL CULTURE MATERIALS AND THE 21ST CENTURY COMPETENCIES - Rita Inderawati; Ismail Petrus; Eryansyah Eryansyah; Meilinda Meilinda (University of Kuningan, 2021)
The needs to know local cultural materials and skills for the future of students in the 21st century motivated researchers to concentrate more on them. In this recent research, an English textbook developed with Palembang local culture in mind and reviewed by students considers student needs. In SMK Negeri 3 Palembang, the travel agent competency program had 35 graders who completed a questionnaire with 45 questions. Questionnaires and semi-structured interviews were used to collect and quantitatively and qualitatively interpret the details. The findings showed: 1) English must be taught through technology to support students; (2) English is essential to students' future careers; (3) no existing English language education materials are included with local Palembang culture; and (4) two main reasons for integrating local Palembang culture into educational materials were to enhance the knowledge of students. Due to the queries, learning resources such as blogs, Twitter, video calls, and voice notes became important for the promotion of skills in the 21st century.